Persistent Unilateral Nephrolithiasis: Do 24-h Urine Parameters Account for It? - Orel Hemo; Miki Haifler; Asaf Shvero; Nir Kleinmann; Dorit E. Zilberman (Journal of Clinical Medicine, 2026)
Background: Bilateral nephrolithiasis is typically attributed to systemic metabolic abnormalities reflected in 24 h urine studies. Yet, some individuals form stones exclusively in one kidney over long-term follow-up, while the contralateral kidney remains unaffected. This study aimed to determine whether differences in urinary metabolites can explain persistent unilateral stone formation. Methods: We retrospectively reviewed our 2011–2024 nephrolithiasis database and analyzed 24 h urine compositions obtained under regular diet and daily activity conditions. Patients were classified into three groups: bilateral stone formers (BSF), unilateral stone formers (USF), and past unilateral stone formers (PUSF)—the latter comprising patients whose stone-forming kidney was either resected or non-functioning, with urine reflecting the contralateral, stone-free kidney. Results: The study included 618 patients in the BSF group, 22 in the USF group, and eight in the PUSF group. The median follow-up duration was 83 months. After correction for multiple comparisons, the only difference between the USF and BSF groups that remained significant was higher urinary calcium in the USF group (269 vs. 184 mg/24 h; adjusted p = 0.03). The PUSF group had lower creatinine and uric acid than the other groups, and lower citrate than the USF group (adjusted p < 0.05); the differences in oxalate did not remain significant after correction. Conclusions: Standard 24 h urine parameters, which reflect combined output from both kidneys, did not account for persistent unilateral nephrolithiasis. This suggests that local renal, molecular, or genetic factors, rather than systemic metabolic differences, may underlie this phenomenon.